COHESION AND COHERENCE IN ADVERTISING DISCOURSE IN TIME MAGAZINE OF NOVEMBER 2009 TO JANUARY 2010 (Universitas Negeri Semarang, 2013)
This study is aimed at finding out the cohesion and coherence in advertising discourse in TIME magazine as well as its implication of the study in teaching reading and writing. The writer used purposive sampling as the method of collecting data. The data were taken from several editions of TIME Magazine published in November 2009 to January 2010. In analyzing the data, the writer used a cohesion theory suggested by Halliday and Hasan (1976). On the contrary in coherence analysis the writer generated Peirce’s semiotic theory of sign (in Short, 2007) and speech act theory proposed by Austin (1962). Thus, in analyzing the aspect of coherence the writer focused on recognizing and identifying the function of headline as well as the pictures with respect to illocutionary meaning and semiotic meaning. The results of such analysis show that there are three cohesive devices frequently used in the advertising discourse. They are lexical cohesion (59.18%) followed by reference (32.65%) and conjunction (8.16%) in which the most presupposed item tends to refer to what is advertised. On the other hand the headlines and images are both coherent with the idea of the written discourse and speech act meaning as suggested by Austin’s theory. The pictures in the advertising discourse have implication on cultural, social and mythical ideology as suggested by Peirce’s theory of sign. Beside to visualize, and to claim the quality of the products they also to represent the hidden ideas in order to create image, prestige and trust in community. Considering to the results of this research, it can be concluded that the understanding of cohesion and coherence for students will greatly affect the ability of students in reading, interpreting and writing a text. In order to improve the students’ proficiency, it is important to introduce variety of texts such as advertising discourse for students especially in Senior High school.